A phase I study of LCL161, a novel oral pan‐inhibitor of apoptosis protein (IAP) antagonist, in Japanese patients with advanced solid tumors. Issue 5 (30th January 2022) - Morita, Sachi; Minami, Hironobu; Mitsuma, Ayako; Toyoda, Masanori; Kiyota, Naomi; Ando, Yuichi
Abstract: Introduction: LCL161 is a novel oral pan‐inhibitor of apoptosis protein (IAP) antagonist. LCL161 enhances paclitaxel activity in cell lines and xenograft models. A phase I study of LCL161 combined with paclitaxel for the treatment of Japanese patients with advanced solid tumors was conducted. Methods: Each patient received oral LCL161 in a single weekly dose on days 1, 8, and 15 of a 21‐day treatment cycle. In the second cycle, patients received a combination treatment with weekly paclitaxel (80 mg/m 2 ) whenever possible. A Bayesian logistic regression model by escalation with the overdose control principle was used. Results: Nine patients were treated with LCL161 at a dose of 600 mg (five patients) or 1200 mg (four patients). Seven patients were treated with LCL161 plus paclitaxel, and two patients received only LCL161 monotherapy. Because this study was terminated early due to a change in the LCL161 development strategy, the maximum tolerated dose (MTD) was not determined. One patient treated with LCL161 monotherapy at a dose of 1200 mg experienced dose limitind toxicity (grade 3 maculopapular rash). Another patient died on day 86 of bacterial pneumonia, which was suspected to be related to the study treatment. The most common serious adverse events were infections and infestations ( n = 3). Conclusion: The present study suggests that the risk of infection may increase when LCL161 is combined with paclitaxel, but other conclusions about the MTD, pharmacokinetic profile, and preliminary activity of the combination of LCL161 plus paclitaxel were not drawn.